2006
DOI: 10.1002/ts.73
|View full text |Cite
|
Sign up to set email alerts
|

Pollen population, viscosity and density of locally produced honey

Abstract: Eight samples of honey, purchased locally, all contained pollen grains of different sizes and shapes. There was a correlation between the pollen population and pollen size, but not between the population and either density or viscosity of the honey. Copyright © 2006 John Wiley & Sons, Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A lot is known all over the world about botanical and ecological origins of honey samples, the honey plants and honey quality. In Nigeria, Sowunmi (1976), Agwu and Akanbi (1985), Adeonipekun (1989), Ayodele et al (2006), Njokuocha and Ekweozor (2007), Adekanmbi and Ogundipe (2009), Adeonipekun (2010Adeonipekun ( , 2012, Ige and Modupe (2010), Aina and Owonibi (2011), Aina et al (2015) are the major works on melissopalynology. These workers have supplied the available information about the botanical and geographical origins and studied the biochemistry of honey, as well as its quality determination across the country.…”
Section: Introductionmentioning
confidence: 99%
“…A lot is known all over the world about botanical and ecological origins of honey samples, the honey plants and honey quality. In Nigeria, Sowunmi (1976), Agwu and Akanbi (1985), Adeonipekun (1989), Ayodele et al (2006), Njokuocha and Ekweozor (2007), Adekanmbi and Ogundipe (2009), Adeonipekun (2010Adeonipekun ( , 2012, Ige and Modupe (2010), Aina and Owonibi (2011), Aina et al (2015) are the major works on melissopalynology. These workers have supplied the available information about the botanical and geographical origins and studied the biochemistry of honey, as well as its quality determination across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Two exceptions given a Misleading results: manufactured honey or the product from feeding the beehives, to which pollen grains are added for the purpose of adulteration and selling it as a pure honey (Fig. 3), this is inconsistent with what Ayodele et al (2006), who considered the presence of pollen as an indication of the originality of honey. From Table (3) indicated that the significant determinant and important factor for the quality of honey produced under the Egyptian conditions during the study period was the proportion of sucrose.…”
Section: Fig 2 : Relationship Between Sucrose Percentage and Pollen Densitymentioning
confidence: 94%
“…Ayodele et al 2 reported that some of the honey that is sold in the market and groceries in Nigeria are molasses (sugarcane syrup). Adulteration of honey does more dangerous to consumers.…”
Section: Introductionmentioning
confidence: 99%